2018
DOI: 10.3390/en11102717
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Innovative Protracted-Finned Counter Flow Heat Exchanger (PFCHE) for an Engine WHR and Its Impact on Exhaust Emissions

Abstract: This article describes and evaluates an Organic Rankine Cycle (ORC) for waste heat recovery system both theoretically as well as experimentally. Based on the thermodynamic analysis of the exhaust gas temperature identified at different locations of the exhaust manifold of an engine, the double-pipe, internally–externally protruded, finned counter flow heat exchanger was innovatively designed and installed in diesel engine for exhaust waste heat recovery (WHR). The tests were conducted to find the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The demand for petroleum product and efficiency in energy conversion devices is increasing because of the increase in industrialization and modernization of the world. 1,2,11,12,[40][41][42]46 The excessive use of fossil-derived fuels such as gasoline in spark ignition (SI) engines has been proven to have a negative effect on our environment, which affects our social well-being. 13,14 The concern on the increasing air pollution and climate change as a result of exhaust gas emissions has mandated the search for environmentally friendly fuel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for petroleum product and efficiency in energy conversion devices is increasing because of the increase in industrialization and modernization of the world. 1,2,11,12,[40][41][42]46 The excessive use of fossil-derived fuels such as gasoline in spark ignition (SI) engines has been proven to have a negative effect on our environment, which affects our social well-being. 13,14 The concern on the increasing air pollution and climate change as a result of exhaust gas emissions has mandated the search for environmentally friendly fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for petroleum product and efficiency in energy conversion devices is increasing because of the increase in industrialization and modernization of the world. ,,,, , The excessive use of fossil-derived fuels such as gasoline in spark ignition (SI) engines has been proven to have a negative effect on our environment, which affects our social well-being. , The concern on the increasing air pollution and climate change as a result of exhaust gas emissions has mandated the search for environmentally friendly fuel. , Also, considering the energy crises and pollution problems today, the use of gasoline and alcohol fuels blend as an alternative fuel in a gasoline engine is becoming necessary. The oxygenate fuels sometimes come in the form of an additive and are being introduced into the main gasoline usually in percentage. ,, The use of fuel additives is being introduced to fuel because some additives improve the engine performance and reduce emissions such as smoke, CO, HC, NOx, SO 2 , and solid particles . Oxygenated fuel is used to improve fuel properties, combustion quality, and octane rating in an SI engine. ,,− The oxygenated fuels commonly used are ethanol, methanol, butanol, propanol, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer and pressure drop are directly proportional to the length of the tube. As the length of the tube increases, more surface area is available to transfer heat compromising high-pressure drop [37]. Therefore, to predict the overall effect of tube length on the heat pump cycle, curves are plotted for EER and COP at various tube lengths as shown in Figure 15a,b and Figure 16.…”
Section: Effect Of Tube Lengthmentioning
confidence: 99%
“…A study conducted on heavy‐duty engines has shown that ~200 s is the usual time taken by the SCR catalyst to reach LOT 28 . Various studies 29,30 have been carried out to improve the catalyst's LOT through thermal management and developing new catalysts. Another factor that drastically reduces the exhaust temperature is the position of the SCR unit in the exhaust system.…”
Section: Introductionmentioning
confidence: 99%
“…27 A study conducted on heavy-duty engines has shown that ~200 s is the usual time taken by the SCR catalyst to reach LOT. 28 Various studies 29,30 have been carried out to improve the catalyst's LOT through thermal management and developing new catalysts.…”
mentioning
confidence: 99%